The Concept of Bughat in Islamic Political Fiqh: A Comparison of Madhhab Shafi'i and Hanafi - Zuairiyah, Zuairiyah; Husna, Fathiyah; Azzahra, Kamila Nayli; Ulyani, Attikah; Siyono, Siyono (Tasyri' : Journal of Islamic Law, 2026)
This study examines the differing perspectives of the Mazhab Shafi’i and Hanafi regarding the concept of bughat (rebellion) within Islamic political jurisprudence. The core issue lies in the variation of criteria, legal treatment, and evidential bases used by the two schools. Using a library research method, analyzing classical sources, relevant hadiths such as those indicating early signs of rebellion (at-thalab), and major fiqh works, the study finds that the Mazhab Shafi’i  requires the presence of military strength, leadership, and legitimate ta’wil to classify a group as bughat, and distinguishes between Muslim and non-Muslim rebels, prioritizing peaceful resolution. In contrast, the Mazhab Hanafi emphasizes governmental stability and allows pre-emptive defensive measures once signs of rebellion appear, without differentiating religious status. These differences stem from each Mazhab’s method of legal derivation. The findings highlight the significant implications of these methodological variations for the application of Islamic public law in contemporary political contexts.